Role and Needs of Hilly Women in Trades - Gautam, U.S.; Chandrakanta,; Singh, D.K. (Indian Journal of Extension Education, 2009)
Rural women play a vital role in domestic and socio-economic life of the society and therefore, national development is not possible without developing this important and substantialy section of our society. Women comprise half of the work force in agriculture especially in developing countries. In India according to 2001 census, female population is 48.27 per cent, out of which 72.72 per cent come from rural areas. The department of rural development, Ministry of Agriculture, Government of India formulated a scheme Development of Women and Children in Rural Areas (D.W.C.R.A.) as a sub scheme of Integrated Rural Development Programme to provide income generating activities to rural women, which will have a positive impact on the economic and multi-nutritional status of the family and also to attempt to provide an organization support in terms of recieving system for the assisted women. The 135 functional women groups were formed out 1350 individual women beneficiaries covered, it is observed that, out of 135 functional women groups, 35 (25.93) sold their products direct to the consumers, 45 (33.33) to whole sale shopkeepers and 55 (40.74) women groups to retail shopkeepers almost equally number divided to the direct to consumers, wholesales shopkeeper and retail of soil.